Language learning strategies and self-efficacy belief in Arabic Language learning: a malaysian context - Mohamad Azrien Mohamed Adnan; Shukeri Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2011)
Teaching and learning is a process that requires active student involvement in the acquisition of knowledge and skills. Students should be assisted in setting individual learning goals. They should also be given the exposure to and guidance in effective learning strategies in order to build a high level of confidence in the learning process. This confidence-building method is especially important for low-performing students and helps them to achieve their specific goals. This paper examines the relationship between language-learning strategies and the self-efficacy belief in Arabic language learning. The objectives of this study are (1) to identify the self-efficacy belief and language learning strategies, (2) to note the effects of self-efficacy on language learning strategies, (3) and to examine the relationship between language learning strategies and students’ self-efficacy. The study uses a questionnaire as the information-gathering instrument, and the participants comprised university students in Peninsular Malaysia, who are studying the Arabic language. A total of 436 students were selected for this study from six universities, namely, Universiti Darul Iman, Universiti Kebangsaan Malaysia, University of Malaya, International Islamic University Malaysia, Universiti Teknologi Malaysia, and Universiti Putra Malaysia. The results indicate that language learning strategies have a strong correlation to self-efficacy beliefs.